MicroRNA Gene Signature for Predicting Mechanisms in Nasopharyngeal Carcinoma: A Case Study on the Potential Application of Circulating Biomarkers - Wardana, Tirta; Oktriani, Risky; Murjayanto, Cita H.; Putri, Denise Utami; Anwar, Sumadi Lukman; Aryandono, Teguh; Haryana, Sofia Mubarika (MicroRNA, 2023)
Background and Aim: Nasopharyngeal Carcinoma (NPC) is an upper respiratory tract cancer prevalent in Southeast Asia and related to chronic EBV infection. microRNAs (miRNAs) regulate gene expression implicated in NPC’s carcinogenesis. However, this circulating RNA molecule’s role and clinical utility remain unknown. Therefore, this study examined the circulation of miRNAs and their association with clinical data. Methods: 160 plasma samples of NPC and 80 non-tumor samples were extracted to evaluate and validate the gene expressions. Quantification expression was performed using relative quantification of qPCR analysis level expression methods. The intrinsic cellular roles involving biological signaling in NPC's oncogenesis using Ingenuity Pathways Analysis (IPA) were also used. Results: The results of the quantification significance profiling of NPC samples revealed decreased miR- 29c-3p (fold change 1.16; p<0.05) and increased 195-5p expression (fold change 1.157; p<0.05). Furthermore, the validation of hsa-miR-29c-3p expression on plasma NPC with known tumor vs. non-tumor and significant changes was also performed using a fold change of 4.45 (medians of 31.45 ± 1.868 and 24.96 ± 1.872, respectively; p<0.0005). miR-29c had a 2.14 fold change correlated with T primary status with a median of 31.99±1.319 and 31.35±2.412, respectively (p<0.05). Stage status with fold change 1.99 also had median levels of 31.98±1.105 and 31.21 ± 2.355, respectively (p-value <0.05). Furthermore, the node’s status for the lower expression of miR-29c with fold change 1.17 had median levels of 32.78 ± 2.221 and 31.33 ± 1.689, respectively (p-value of 0.7). Bioinformatics analysis established the roles and functions of miR-29 in NPC progression, cell death and survival, cellular development, cellular function, and cell maintenance by inhibiting COL4A, PI3K, VEGFA, JUN, and CDK6. Conclusion: Overall, we conclude that decreased miR-29c expression is associated with poor clinical status and might inhibit NPC's five target genes.
Keywords: MicroRNA